Comprehensive characterization of poplar HSP20 gene family: genome-wide identification, stress-induced expression profiling, and protein interaction verifications - Lincui Shi; Yude Kang; Ling Ding; Liejia Xu; Xiaojiao Liu; Anmin Yu; Aizhong Liu; Ping Li (BMC Plant Biology)
Abstract Background Heat shock proteins (HSP20s) are crucial components in plant stress responses, acting as molecular chaperones to safeguard cellular integrity and prevent abnormal protein aggregation. While extensive research has been conducted on HSP20s in various plant species, limited information is available regarding the HSP20 protein family in poplar (Populus yunnanensis), a species of significant ecological and economic importance native to southwestern China. Results To elucidate the distribution, structural features, and functional characteristics of HSP20 proteins in P. yunnanensis, a combination of bioinformatics tools and experimental validation was utilized. A total of 53 PyHSP20s were identified within the P. yunnanensis genome and classified into 12 subfamilies: CI, CII, CIII, CIV, CV, CVI, CVII, MI, MII, ER, CP, and Px containing 24, 1, 1, 1, 2, 2, 14, 3, 1, 1, 2, and 1 HSP20 proteins, respectively. Classification was based on subcellular localization and phylogenetic relationships, revealing subfamilies with varying exon–intron structures and conserved motifs. The 3D structures analysis showed significant differentiation, with the CI subfamily PyHSP20s exhibiting 8 β-sheets, compared to 7 β-sheets in other subfamilies. Additionally, the N-terminal arms displayed heterogeneity in length and sequence. The 53 PyHSP20s were unevenly distributed across 15 chromosomes, with tandem segmental duplications explaining the expansion of subfamilies, particularly CI, CV, CVI, and CVII. The analysis of cis-elements associated with stress response and hormone regulation underscored the critical role of PyHSP20 in stress adaptation. Expression profiling via database analysis and qRT-PCR confirmed the responsiveness of PyHSP20s to multiple stressors, including salt, mannitol, drought, heat, and abscisic acid (ABA). Furthermore, Yeast Two-Hybrid (Y2H) assays demonstrated potential regulatory interactions between PyHSP20s and other functional proteins involved in stress responses. Conclusions These findings provide a comprehensive understanding of the classification, structural differentiation, and functional roles of PyHSP20s in P. yunnanensis, thereby establishing a foundation for future functional investigations into this protein family.